The application of the Media Flow Card is To Improve the Learning Outcomes of English Language Students In Class VII MTs Subulussalam Sumberjo Kabupaten Labuhanbatu Selatan - Rika Syahmewah Munthe (CV. AFDIFAL MAJU BERKAH, 2022)
This study was conducted to improve the learning outcomes with the application using the application flow card is to improve the learning outcomes of English Language students in class VII MTs Subulussalam Sumberjo, kabupaten labuhanbatu Selatan, Research is done by direct observation of the teacher (penilitan) and the student, observer of the implementation of the research carried out by two research associates. Observations were done on 50 students. The Indicator of the success of the research include: the percentage of the research results, mastery learning, and the results of the observation of student activity. The results of this study show that the average value of the pretest of students who referred to the criteria thoroughly studied. The percentage of mastery learning students in the first cycle of 52 %, this has not yet reached mastery criteria in classical because it has not reached > 85%. In the second cycle obtained an average value of student learning outcomes by 83,18 and there are 46 students are included in the kretireia thorough in learning. The percentage of mastery learning students in the second cycle of 92% and reached the criteria of the classical completeness based on the average percentage of students who are active in cycle I and cycle II obtained the increased activity of students, namely cycle I the average level of the percentage of active students that 51,26% and in cycle II increased to 76,5 % from the above explanation can be concluded that the research can improve student learning outcomes.